Feminist Book Publishing Today. Issue 3 (2nd October 2021) - Bakare-Yusuf, Bibi; Dosekun, Simidele
Abstract: In this piece, Bibi Bakare-Yusuf, publisher of Cassava Republic Press based in Abuja (Nigeria) and London (UK), discusses with Simidele Dosekun her founding and continued visions for the press, how these translate into the daily management and operations of the business, and the opportunities and challenges publishing presents for feminist, Black and African political purposes, including transnationally. We also discuss what it means to run and brand a feminist business in a contemporary cultural climate in which feminism is said to be 'popular'.